2020
DOI: 10.1186/s12889-020-09756-5
|View full text |Cite
|
Sign up to set email alerts
|

A confirmatory factor analysis of the knowledge, attitude and practice questionnaire towards prevention of respiratory tract infections during Hajj and Umrah

Abstract: Background Respiratory tract infections are one of the common infection associated with Hajj pilgrimage that is of great public health and global concern. This study is aimed at determining the factor structure of the knowledge, attitude, and practice questionnaire for the prevention of respiratory tract infections during Hajj by confirmatory factor analysis (CFA). Methods A multistage cluster sampling method was conducted on Malaysian Umrah pilgri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…In our study, the NL-SF12 maintained the initial scale's conceptual framework of six dimensions. Its' structural validation was assessed using CFA, which has been widely used to evaluate the structural validity of a scale (40,54,55). The CVI of >0.9 indicated that the NL content was consistent.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the NL-SF12 maintained the initial scale's conceptual framework of six dimensions. Its' structural validation was assessed using CFA, which has been widely used to evaluate the structural validity of a scale (40,54,55). The CVI of >0.9 indicated that the NL content was consistent.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 23 , 26–28 For instance, recent studies among Umrah pilgrims reported that the uptake rate of influenza and pneumococcal vaccinations were 14.5–51% and 12–27.6%, respectively. 21 , 23 , 25 , 26 In light of the above, the small number of respondents in our study and the potential for recall bias, our results are likely to be an overestimation, particularly for non-compulsory vaccinations.…”
Section: Discussionmentioning
confidence: 76%
“…Rates of vaccination with the mandatory meningococcal vaccine were reported to be high among Hajj pilgrims, but lower among Umrah pilgrims. 15 , 21 , 25 One study in 2019 found that only 41.3% of Umrah pilgrims reported meningococcal disease vaccination, while the rate was even lower (30%) among Malaysian pilgrims in 2018. 21 , 25 For other vaccines, studies from both Hajj and Umrah report a low uptake of non-compulsory vaccination among pilgrims, although the uptake is slightly higher among the at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the EFA is used to establish the most appropriate factor structure of the questionnaire based on the pattern-linearity of the factor loadings, the application of CFA is worthwhile to complement the construct validity by confirming the factorial structure and their respective items identified in the EFA [ 41 44 ]. In the current study, the four-factor structure was established by CFA, indicating the satisfactory fitting of the suggested models.…”
Section: Discussionmentioning
confidence: 99%